Production of Bio-Polymer Structures by Soft Molding Method with Biomimetic Approach - Arslanhan, Melike; Eroğlu, Murat; Kaykılarlı, Cantekin; Şam Parmak, Ebru Devrim (My University, 2021)
Biomimetic is the name of the approach that seeks sustainable solutions to the problems, taking the perfect functioning of nature for millions of years. The interest shown in biomimetic surfaces, inspired by multi-scale structures found in many plants and animals, is increasing day by day. Especially the unique wettability properties of the lotus leaf and rose petal. In this study, inspired by the structures of lotus leaf and rose petal, using the soft casting method with dental bio-polymer materials, structures with pillar dimensions of micron (µm) and millimeter (mm) were produced. These structures are replicated from two commercial products with different pillar lengths and different pillar shapes, mushroom and conical needle tips. Surface topographies of the replicated final products were analyzed by optical and stereo microscopes. Contact angles were tested to examine the wettability properties of the surfaces. According to the microscope results obtained, the demolding process, which is the riskiest step of the replication process, was successfully passed thanks to soft casting. Contact angle analysis showed that different pillar lengths and different pillar shapes changed the wettability properties of the replicated final product. The replicated mushroom-shaped micron-scale pillar structures exhibited a rose-petal effect and hydrophobic properties (approximately 1000) with only a single-scale configuration, while conical needle-shaped pillars of millimeter (mm) scale did not show any specific wetabilitty property.
Keywords: Biomimetics; Rose-petal; Bio-polymer; Soft molding